ПЕРЕТВОРЮВАЧ АСИНХРОННОГО ЕЛЕКТРОПРИВОДА І ЕЛЕКТРОПРИВОДА ПОСТІЙНОГО СТРУМУ - Чепкунов, Р.А. (Інститут електродинаміки Національної академії наук України, 2024)
A converter is considered that canprovide control of both anasynchronous electric drive and a DC electric drive. In an asynchronous electric drive control of a three-phase frequency converter by reactive power; in a DC electric drive the armature voltage is formed by PWM modulation of two arms of the frequency converter, and the voltage of the field winding is PWM modulated by the third arm of the converter. Ensures high-quality control of electric drives. Ref. 10, fig. 3.